Effects of supine and -6° head-down tilt posture on cardiovascular and exercise performance - Ade, Carl J. (Kansas State University, 2008)
Background and Aim: Long-term microgravity exposure, via spaceflight or -6° head-down tilt bedrest, has been shown to produce significant cardiovascular deconditioning and decreases in exercise performance. However, there is little known about how acute microgravity exposure influences the cardiovascular system’s ability to adjust to increases in physical work. Therefore, the aim of this study was to compare cardiovascular and exercise performance during acute upright, supine and -6° head-down tilt positions. Methods: Seven healthy inactive men performed maximal cycle exercise (VO2peak) tests in the upright, supine, and -6° head-down tilt on separate days. Oxygen consumption and heart rate were measured continuously throughout the testing procedures. Cardiac output (acetylene exhalation technique) was measured periodically and interpolated to the 100-watt work rate. Stroke volume was calculated from cardiac output and heart rate data. Results: Peak oxygen uptake and heart rate were significantly decreased in the supine and -6° head-down tilt positions compared to the upright (VO2peak 2.01±0.46, 2.01±0.51 versus 2.32±0.61 L/min respectively; peak heart rate 161±13, 160±14 versus 172±11 bmp). However, cardiac output at 100-watts was similar in all three-exercise positions. Calculated stroke volume at 100-watts was significantly higher in the -6° head-down tilt position compared to the upright position (76.6±4.7 versus 71.2±4.5, ml). Conclusion: These results suggest that exercise capacity is immediately decreased upon exposure to a microgravity environment, prior to any cardiovascular deconditioning. Therefore, an astronaut’s exercise performance should be evaluated with exercise tests in the -6° head-down tilt position prior to space flight in order to establish a baseline response.
Keywords: Cardiovascular; Exercise; Microgravity; Biology, Anatomy (0287); Biology, Animal Physiology (0433); Health Sciences, Medicine and Surgery (0564)